+0  
 
0
480
1
avatar

Why is it (-2)x4+18/-3+12+(-(-2)x2-5)(-(-5)+2-5) =-4?

 Jun 6, 2014

Best Answer 

 #1
avatar+3451 
+5

Well, if you just work it out, it will show you why (-2)x4+18/-3+12+(-(-2)x2-5)(-(-5)+2-5) = -4.

(-2)x4+18/-3+12+(-(-2)x2-5)(-(-5)+2-5) = -4

(-8)+(-6)+12+(-(-2)x2-5)(-(-5)+2-5) = -4

(-14)+12+(-(-2)x2-5)(-(-5)+2-5) = -4

(-2)+(+(+2)x2-5)(+(+5)+2-5)= -4

(-2)+(-1)(2) = -4

(-2)+(-2) = -4

-4 = -4

 Jun 6, 2014
 #1
avatar+3451 
+5
Best Answer

Well, if you just work it out, it will show you why (-2)x4+18/-3+12+(-(-2)x2-5)(-(-5)+2-5) = -4.

(-2)x4+18/-3+12+(-(-2)x2-5)(-(-5)+2-5) = -4

(-8)+(-6)+12+(-(-2)x2-5)(-(-5)+2-5) = -4

(-14)+12+(-(-2)x2-5)(-(-5)+2-5) = -4

(-2)+(+(+2)x2-5)(+(+5)+2-5)= -4

(-2)+(-1)(2) = -4

(-2)+(-2) = -4

-4 = -4

NinjaDevo Jun 6, 2014

60 Online Users

avatar
avatar
avatar
avatar
avatar
avatar